Portrait photograph of an unidentified man (Cambridgeport, MA) - Thayer, Alexander Wheelock, 1817-1897 (previous owner):::Collector::::::::::::; Warren (photographer):::Photographer:::::::::::: (Warren; United States; Cambridgeport, MA, 2023)
Portrait photograph of an unidentified man (undated) by Warren, Post Office Block, Cambridgeport, MA, from the personal collection of Alexander Wheelock Thayer.